2018
DOI: 10.1021/acs.inorgchem.8b00867
|View full text |Cite
|
Sign up to set email alerts
|

NIR Downconversion and Energy Transfer Mechanisms in Tb3+/Yb3+ Codoped Na5Lu9F32 Single Crystals

Abstract: Tb/Yb codoped NaLuF single crystals with near-infrared (NIR) emission are achieved by an improved Bridgman approach. Energy transfer from Tb to Yb ions is affirmed by the photoluminescence (PL) emission spectra and decay curves characterization. On the basis of the analysis of energy transfer rate dependence on the Yb concentration, the interaction between Tb and Yb ions in NaLuF single crystals is confirmed through the one-to-one energy transfer process. Results demonstrate that the prepared NaLuF single crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…Typically, the Tb→Yb cooperative energy transfer is considered to be the most probable relaxation pathway from the 5 D 4 excited state of the Tb 3+ ion since the probability of the non-radiative multi-phonon relaxation needed to compensate the energy gap between the 5 D 4 (Tb 3+ ) and 3 F 5/2 (Yb 3+ ) excited states, is small. In some materials the one-to-one energy transfer mechanism can dominate over the down-conversion process [33]. As was mentioned above, the concentration of the REE in the t-ZrO 2 crystalline phase decreased significantly when compared to the pristine glass, i.e., the possibility of finding an Yb-Yb pair in the nearest sphere of Tb 3+ is much smaller.…”
Section: T-zro2mentioning
confidence: 92%
“…Typically, the Tb→Yb cooperative energy transfer is considered to be the most probable relaxation pathway from the 5 D 4 excited state of the Tb 3+ ion since the probability of the non-radiative multi-phonon relaxation needed to compensate the energy gap between the 5 D 4 (Tb 3+ ) and 3 F 5/2 (Yb 3+ ) excited states, is small. In some materials the one-to-one energy transfer mechanism can dominate over the down-conversion process [33]. As was mentioned above, the concentration of the REE in the t-ZrO 2 crystalline phase decreased significantly when compared to the pristine glass, i.e., the possibility of finding an Yb-Yb pair in the nearest sphere of Tb 3+ is much smaller.…”
Section: T-zro2mentioning
confidence: 92%
“…28,29 UCNPs not only show upconversion luminescence (UCL), but they have even more efficient downconversion luminescence (DCL) in the near infrared (NIR) which make them ideal candidates for NIR to NIR-DC bioimaging applications. 30,31 Interestingly it has also been reported that UCL and DCL emission depend on the size of the NaYF 4 :Yb 3+ ,Er 3+ nanoparticles. UCL intensity increase as the nanoparticles' size increases, whereas in DCL, the most efficient emission occurs for diameters ranging from 15nm to 40 nm when high excitation intensities are used.…”
Section: Introductionmentioning
confidence: 94%
“…The main energy transfer is Ln → Yb 3+ /Er 3+ /Tm 3+ (Ln: Eu 2+ , Ce 3+ , Tb 3+ , Yb 3+ , Er 3+ , Tm 3+ ). 290 Among them, Ln ions mainly absorb n-UV or blue light. Because the excited energy of Ln is much higher than that of Yb 3+ /Er 3+ /Tm 3+ ions, there are two energy transfer channels from the excited level of Ln ions to that of the Yb 3+ /Er 3+ /Tm 3+ ion.…”
Section: Energy Transfer Induced Photoluminescence Enhancement and Tu...mentioning
confidence: 99%
“…In quantum-cutting NIR luminescent materials, energy transfer is indispensable. The main energy transfer is Ln → Yb 3+ /Er 3+ /Tm 3+ (Ln: Eu 2+ , Ce 3+ , Tb 3+ , Yb 3+ , Er 3+ , Tm 3+ ) . Among them, Ln ions mainly absorb n-UV or blue light.…”
Section: Energy Transfer Induced Photoluminescence Enhancement and Tu...mentioning
confidence: 99%